Atomically dispersed Ru in Pt3Sn intermetallic alloy as an efficient methanol oxidation electrocatalyst. Issue 17 (1st February 2021) - Yang, Tianyi; Qin, Fengjuan; Zhang, Shuping; Rong, Hongpan; Chen, Wenxing; Zhang, Jiatao
Abstract : A Ru–Pt3 Sn NC catalyst composed of atomically dispersed Ru atoms shows enhanced performance in methanol electroxidation, which is ascribed to the stable intermetallic structure and active surface structure, as well as the synergy among Pt, Sn and Ru. Abstract : We successfully fabricate a novel concave nanostructure that is composed of atomically dispersed Ru atoms in Pt3 Sn nanoconcaves (Ru–Pt3 Sn NCs), which shows enhanced performance in methanol electroxidation compared to commercial Pt/C. This could be ascribed to the stable intermetallic structure and active surface structure, as well as the synergy among Pt, Sn and Ru.